Collection mode choice of spent electric vehicle batteries: considering collection competition and third-party economies of scale - Li, Xin (Scientific reports, 2022)
With the rapid development of the electric vehicle (EV) industry, the recycling of spent EV batteries has attracted considerable attention. The establishment and optimization of the collection mode is a key link in regulating the recycling of spent EV batteries. This paper investigates an EV battery supply chain including an EV manufacturer, an EV retailer, and a third-party collector and analyzes three dual-channel collection modes. The optimal pricing and collection decisions of the three dual-channel collection modes are obtained and compared. The collection mode choice strategy and the effects of third-party economies of scale are explored. Three interesting insights are derived: (i) Third-party economies of scale can improve the collection rate of spent EV batteries and the profit of the supply chain. (ii) The optimal collection mode choice depends on the intensity of collection competition and the third-party economies of scale. (iii) When the intensity of collection competition and the third-party economies of scale are high enough, the EV retailer and the third-party dual-channel collection mode is the optimal mode; otherwise, the EV manufacturer and the EV retailer dual-channel collection mode is optimal.